2019
DOI: 10.1177/1687814018823356
|View full text |Cite
|
Sign up to set email alerts
|

Energy performance and flow characteristics of a multiphase pump with different tip clearance sizes

Abstract: Deep sea oil resources worldwide possess great potential for exploration; however, multiphase medium technology requires urgent development. The multiphase pump has achieved great success as one of the most advanced machinery in underwater oil and gas exploration. Tip clearance is inevitable between the rotating and stationary components of the multiphase pump. In this study, tip clearance sizes of 0.0, 0.2, 0.5, and 0.8 mm are selected to investigate the effect of tip clearance on energy performance and flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…Next, the tip leakage vortex (TLV) occurs [8,9]. The TLV increases the hydraulic loss in the passage and weakens the hydraulic performance and efficiency, even causing vibration and noise, which has a considerable effect on the operation stability of pumps [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Next, the tip leakage vortex (TLV) occurs [8,9]. The TLV increases the hydraulic loss in the passage and weakens the hydraulic performance and efficiency, even causing vibration and noise, which has a considerable effect on the operation stability of pumps [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…According to the results, the total radial force on the principal axis harbored close association to the fluctuation of mass flow rate within each single flow passage and the radial force upon the blade PS decreased as the tip clearance increased. Zhang J S. et al [14] selected tip clearance sizes of 0.0, 0.2, 0.5, and 0.8 mm for investigating the effects of tip clearance oriented with energy performance and flow characteristics of a multiphase pump. As the results demonstrated, the dominant frequencies and maximum amplitudes of pressure fluctuation rose were rising along with the growth in tip clearance.…”
Section: Introductionmentioning
confidence: 99%
“…Many research results on tip clearance flow have achieved by high-speed photography and PIV; however, due to the high cost, long period and difficulty in measuring in the tip region using experiment method, numerical simulation is still the main method to investigate the tip leakage flow at present. Zhang, J et al 16 studied the effect of different tip clearances on the energy and flow characteristics in the multiphase pump based on the shear stress transport (SST) k-x turbulence model. The results showed that the tip clearance increase proportionally with a entrainment strength between the tip leakage flow and the main flow along the leakage rate.…”
Section: Introductionmentioning
confidence: 99%